The role of tempering conditions and Cr content on the microstructure and mechanical performance of 0.16C-5.5Mn steel - Demir, Fatih; Eroğlu, Mehmet (Bingol University, 2026)
In this paper, the role of tempering conditions and Cr content on the microstructure and mechanical performance of 0.16C-5.5Mn medium manganese steel is discussed. For this purpose, various analyses were applied to 0.16C-5.5Mn steels with 0% Cr and 1.2% Cr content for microstructural characterization. The results obtained showed that the tempering process produced a microstructure consisting of ferrite and fine acicular carbides dispersed in the tempered martensite matrix in 0.16C-5.5Mn steel. It was also observed that the retained austenite phase persisted in the microstructure after tempering. In addition, the Cr content in 0.16C-5.5Mn steel improved the stability of the retained austenite phase after tempering. When all these results were correlated with the data obtained from mechanical tests, it was observed that tempering treatment at low temperatures and Cr content in the steel composition significantly improved the combination of tensile strength and total elongation (TS×TE) of 0.16C-5.5Mn medium manganese steel.

Bu makalede, temperleme koşullarının ve Cr içeriğinin 0.16C-5.5Mn orta manganlı çeliğinin mikroyapısı ve mekanik performansındaki rolü ele alınmıştır. Bu amaçla imal edilen %0 Cr ve %1.2 Cr içerikli 0.16C-5.5Mn çeliklerine mikroyapı karakterizasyonu amacıyla çeşitli analizler uygulanmıştır. Elde edilen sonuçlar temperleme işleminin 0.16C-5.5Mn çeliğinde temperlenmiş martenzit matrisinde dağılmış ferrit ve ince iğnemsi karbürlerden oluşan bir mikroyapı meydana getirdiğini göstermiştir. Ayrıca, kalıntı östenit fazının temperleme sonrasında da mikroyapıda varlığını sürdürdüğü görülmüştür. Ek olarak, 0.16C-5.5Mn çeliğindeki Cr içeriği kalıntı östenit fazının temperleme sonrasındaki kararlılığını geliştirmiştir. Tüm bu sonuçlar mekanik testlerden elde edilen veriler ile ilişkilendirildiğinde, düşük sıcaklıklardaki temperleme işleminin ve çelik bileşimindeki Cr içeriğinin 0.16C-5.5Mn orta manganlı çeliğinin çekme mukavemeti ile toplam uzama (TS×TE) kombinasyonunu belirgin bir şekilde geliştirdiği gözlemlenmiştir.
Temperleme koşullarının ve Cr içeriğinin 0.16C-5.5Mn çeliğinin mikroyapısı ve mekanik performansındaki rolü
Keywords: Marine Main and Auxiliaries; Gemi Ana ve Yardımcı Makineleri